Polyester base fabric for air-bag
A polyester base fabric for airbags, optimized for durability and deployment performance, addresses the high cost of nylon 6,6 fibers by meeting specific scrub test and performance criteria, ensuring effective restraint and mechanical properties post-aging.
Patent Information
- Application Number
- JP2024161404
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing airbag base fabrics made of nylon 6,6 fibers are expensive, and there is a need for a cost-effective alternative that maintains high restraint performance and mechanical properties even after aging.
A polyester base fabric designed to withstand 400 scrub tests after aging at 70°C, 95% RH, and 408 hours, with specific energy allowance (EA) and restraining capacity usage rate (RR) requirements, coated with silicone resin, and optimized crimp rate and fineness to enhance durability and deployment performance.
The polyester base fabric provides high restraint performance and maintains mechanical properties even after aging, reducing costs while ensuring safe and effective deployment of airbags.
Smart Images

Figure 2025004021000003 
Figure 2025004021000001 
Figure 2025004021000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester base fabric for airbags. More specifically, the present invention relates to a polyester base fabric for airbags that has high restraining performance for receiving an occupant when deployed while maintaining the mechanical properties of an airbag, and further, maintains the performance at a high level even when it changes over time. [Background technology]
[0002] In recent years, airbags have been widely installed in automobiles as passenger safety protection devices, and their installation locations have expanded to include driver's seat, passenger seat, thigh protection airbags built into the seat, and curtain airbags deployed along the side windows, and the amount of airbag fabric used per automobile tends to increase. The fabrics that currently make up airbags are mainly made of polyamide fibers, particularly nylon 6,6 fibers, which have properties suitable for airbag fabrics, but nylon 6,6 fibers are relatively expensive, and the cost burden is increasing as airbags are used more widely. Therefore, there is a demand for fabrics made of polyester fibers, which have a lower raw yarn cost than nylon 6,6 fibers.
[0003] However, airbag fabrics are required to have various properties to protect automobile occupants. For example, airbag fabrics are required to have not only deployability but also various mechanical properties necessary to receive occupants, and are required to maintain sufficient performance even in accelerated aging tests assuming a usage environment. In order to meet these requirements, for example, Patent Document 1 proposes an airbag fabric intended to maintain performance after aging by specifying the kneading resistance performance after wet heat deterioration. However, all of these fabrics are made of polyamide such as nylon 6,6, and polyester fabrics are not substantially disclosed. Compared to nylon 6,6 fiber, the properties of polyester fiber are less favorable for use in airbag fabrics, and airbag fabrics using polyester fiber are not yet widely used. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] China Patent Publication 103132333B Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made against the background of the problems of the conventional technology described above, and uses polyester fibers that can reduce the cost burden, and has high restraining performance for receiving an occupant at the time of deployment while maintaining the mechanical properties of an airbag base fabric. It is an object of the present invention to provide a polyester base fabric for airbags that maintains the performance at a high level even if it changes over time. [Means for solving the problem]
[0006] As a result of intensive research by the present inventors to solve the above problems, the present invention has finally been completed.
[0007] 1. A polyester base fabric for airbags, characterized in that the number of scrub tests after 408 hours of aging treatment at 70°C and 95% RH is 400 or more. 2. The polyester base fabric for airbags according to the above item 1, having an energy allowance (EA) per unit weight calculated by the following formula 1 of 5.0 (J / g) or less. Equation 1: EA(J / g)=(EW+EF) / W where EW (mJ / cm 2 ) is the hysteresis energy per unit surface area in the warp direction when the fabric is stretched to a stress of 120 N / cm and then relaxed to a stress of 0 N / cm. EF(mJ / cm 2 ) is the hysteresis energy per unit surface area in the weft direction when stretched to a stress of 120 N / cm and then relaxed to a stress of 0 N / cm. W (g / m 2 ) is the weight of the base fabric per unit area, Each is shown. 3. The polyester base fabric for airbags according to 1 or 2 above, having a restraint capacity utilization rate (RR) of 85% or more as calculated by the following formula 2: Equation 2: RR(%)=RW / BW+RF / BF where RW (mm) is the stretch of the base fabric in the warp direction when loaded at 120N / cm. BW (mm) is the elongation of the base fabric at break in the warp direction, RF (mm) is the elongation of the base fabric in the weft direction when loaded at 120N / cm. BF (mm) is the elongation of the base fabric at break in the weft direction, Each is shown. 4. The polyester base fabric for airbags according to any one of 1 to 3 above, which has an initial scrub test count of 500 or more. 5. The polyester base fabric for airbags according to any one of 1 to 4 above, having a cover factor of 1,900 to 2,600. 6. Weight is 300g / m 2 6. The polyester base fabric for an airbag according to any one of 1 to 5 above, which is as follows: 7. The resin used is a silicone resin and has a density of 5 g / m 2 More than 50g / m 2 The polyester base fabric for an airbag according to any one of 1 to 6 above, which is coated with the following: 8. A polyester base fabric for airbags according to any one of 1 to 7 above, which is composed of polyester fibers having a total fineness of 200 to 555 dtex and a single yarn fineness of 6.0 dtex or less. 9. The polyester base fabric for airbags according to any one of 1 to 8 above, which has a dry heat shrinkage rate of 3% or less. 10. The polyester base fabric for airbags according to any one of 1 to 9 above, having a weft curl rate of 3% or less. 11. The polyester base fabric for airbags according to any one of 1 to 10 above, having a VOC content of 100 ppm or less. 12. A polyester base fabric for airbags according to any one of 1 to 11 above, wherein the crimp rate of the yarns constituting the base fabric is 1.0% to 12.0% for both the warp and weft yarns. Effect of the Invention
[0008] According to the present invention, even if a base fabric using relatively inexpensive polyester fibers is used, when it is used in an airbag, it is possible to provide a base fabric having various properties for protecting automobile occupants at a high level. It is possible to provide a base fabric. [Brief description of the drawings]
[0009] [Figure 1] FIG. 13 is a diagram for explaining a method for measuring the fabric twist rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The technical concept of the present invention mainly consists of three elements: the number of scrub tests after aging treatment at 70°C and 95% RH for 408 hours is 400 or more, the energy allowance (EA) per unit weight calculated from the hysteresis energy of the base fabric at a stress of 120 N / cm is 5.0 J / g or less, and the restraint capacity utilization rate (RR) calculated from the ratio of the elongation at 120 N / cm to the elongation at break is 85% or more.
[0011] The present inventors conducted a detailed analysis of polyester fabrics and polyamide fabrics such as nylon 6,6, and found that, if the number of scrub tests after 408 hours of aging treatment at 70°C and 95% RH is 400 or more, an airbag fabric comparable to a polyamide fabric can be obtained. A more preferable number of scrub tests after 408 hours of aging treatment at 70°C and 95% RH is 450 or more. There is no particular limit to the upper limit of the number of scrub tests, but it is preferably 2500 or less, more preferably 2000 or less, in terms of the relationship between the airbag fabric and the coating agent used.
[0012] According to the analysis by the inventors, a typical polyester base fabric tends to have inferior crumple resistance after wet heat degradation compared to a polyamide base fabric. This is believed to be because the bond between the silicone coating, which is generally used for coating airbags, and polyester is more susceptible to the effects of moisture than nylon 6,6.
[0013] There are no particular limitations on the means for obtaining a polyester base fabric that can withstand 400 or more scrub tests after aging treatment at 70° C. and 95% RH for 408 hours, and the means may be, for example, modification of the surface of polyester fibers.
[0014] However, in order to effectively utilize the low cost characteristic of polyester fibers, it is recommended to increase the crimp rate of the polyester fibers constituting the base fabric, as described below. The higher the crimp rate, the more irregularities there are in the surface structure of the base fabric, and the inventors have found that this increases the surface area where the coating agent comes into contact with the polyester base fabric, thereby improving the crumpling resistance after moist heat degradation. This eliminates the need for surface modification of the polyester fibers, and therefore makes it possible to obtain a polyester base fabric for airbags that can withstand moist heat degradation at low cost.
[0015] In the present invention, the number of scrub tests after aging treatment of the base fabric for 408 hours at 70°C and 95% RH is measured according to ISO 5981. Specifically, a test piece after aging treatment for 408 hours at 70°C and 95% RH is fixed to a scrub tester using a thermo-hygrostat, and a test is performed under an initial load of 1 kgf, and the degree of peeling of the coating of the sample after the test is visually confirmed.
[0016] The polyester base fabric for airbags of the present invention preferably has an energy allowance (EA) per unit weight, calculated by the following formula 1, of 5.0 (J / g) or less. Equation 1: EA(J / g)=(EW+EF) / W where EW (mJ / cm 2) is the hysteresis energy per unit surface area in the warp direction when the fabric is stretched to a stress of 120 N / cm and then relaxed to a stress of 0 N / cm. EF(mJ / cm 2 ) is the hysteresis energy per unit surface area in the weft direction when stretched to a stress of 120 N / cm and then relaxed to a stress of 0 N / cm. W (g / m 2 ) is the weight of the base fabric per unit area, Each is shown.
[0017] Here, the value of "120 N / cm" corresponds to the maximum stress applied to the airbag fabric during deployment. In other words, the energy tolerance when the airbag is stretched to a stress of 120 N / cm and then relaxed to a stress of 0 N / cm indicates the degree to which the airbag fabric can tolerate the energy received from the inflator during the deployment behavior of the airbag. The smaller this energy tolerance, the better the deployment performance, and furthermore, it is an important factor from the viewpoint of suppressing the bursting of the airbag due to the energy received by the fabric.
[0018] If the energy allowance (EA) per unit weight is 5.0 J / g or less, the airbag obtained can use the energy emitted from the inflator at the time of deployment without waste, and not only can it be deployed quickly, but also the risk of bursting due to breakage of the base fabric can be suppressed because the energy allowance of the base fabric is small. A more preferable energy allowance (EA) per unit weight is 4.0 J / g or less. On the other hand, there is no particular limit on the lower limit of the energy allowance (EA) per unit weight, but it is preferably 0.1 J / g or more, and more preferably 0.5 J / g or more, in view of the characteristics of polyester fibers.
[0019] The polyester base fabric for airbags of the present invention preferably has a restraining capacity utilization rate (RR) calculated by the following formula 2 of 85% or more. Equation 2: RR(%)=RW / BW+RF / BF where RW (mm) is the stretch of the base fabric in the warp direction when loaded at 120N / cm. BW (mm) is the elongation of the base fabric at break in the warp direction, RF (mm) is the elongation of the base fabric in the weft direction when loaded at 120N / cm. BF (mm) is the elongation of the base fabric at break in the weft direction, Each is shown. A more preferable restraining capacity utilization rate (RR) is 90% or more. On the other hand, although there is no particular upper limit for the restraining capacity utilization rate (RR), it is preferably 200% or less in view of the characteristics of the base fabric, and more preferably 150% or less.
[0020] The present inventors have found that polyester fabrics tend to burst more easily than polyamide fabrics. This is because conventional polyester fabrics are harder than polyamide fabrics such as nylon 6,6, and the stress-elongation curve of polyester fabrics reaches high stress in a shorter elongation than nylon 6,6, i.e., the fabric has higher rigidity, and therefore has inferior elongation performance compared to nylon 6,6, and cannot tolerate the energy at the time of deployment, which is thought to make the fabric more likely to burst.
[0021] The restraint capacity utilization rate (RR), defined as the "elongation at 120 N / cm relative to the breaking elongation," indicates the slope of the stress-elongation curve in the airbag's deployment behavior. In other words, the inventors have found that the higher the restraint capacity utilization rate (RR), the greater the elongation of the base fabric during deployment, and therefore the risk of the airbag bursting during deployment due to rapid elongation of the base fabric can be reduced.
[0022] From the viewpoint of ensuring safety during deployment, the initial number of scrub tests for the polyester airbag fabric of the present invention is preferably 500 or more, more preferably 550 or more. There is no particular upper limit to the number of scrub tests, but in consideration of the relationship between the polyester fabric and the coating agent used, it is preferably 3000 or less, more preferably 2500 or less.
[0023] In the present invention, the initial number of scrub tests of the base fabric is measured according to ISO 5981. Specifically, a test piece is fixed to a scrub tester, and the test is performed under an initial load of 1 kgf, and the degree of peeling of the coating of the sample after the test is visually confirmed.
[0024] Considering the restraining capacity usage rate (RR) and the number of scrub tests, the cover factor (CF) of the polyester base fabric for airbags of the present invention is preferably 1900 to 2600. A more preferable lower limit of the cover factor (CF) is 2200, and a more preferable upper limit of the cover factor (CF) is 2500. The CF was calculated by the following formula. CF = (√A) × (W1) + (√B) × (W2) In the formula, A and B respectively indicate the thickness (dtex) of the warp and weft threads, and W1 and W2 respectively indicate the warp density and weft density (lines / 2.54 cm).
[0025] The polyester base fabric for airbags of the present invention has a basis weight of 300 g / m 2 It is preferably 233 g / m or less. More preferably, it is 233 g / m 2 Within this range, the airbag base fabric can be easily made lighter, and the storability in the module can be improved.
[0026] The lower limit of the basis weight of the polyester base fabric for airbags of the present invention is not particularly limited as long as it is within a range that ensures satisfactory breathability during use of the airbag. 2 If the thickness is equal to or greater than this, it is considered that the material has sufficient breathability for use as an airbag.
[0027] In the present invention, the basis weight is measured according to JIS L 1096 8.3. Two test pieces of about 200 mm x 200 mm are taken from the sample, and the bone dry mass (g) of each is measured. 2 Mass per unit (g / m 2 ) and calculate the average to obtain the basis weight.
[0028] In the polyester base fabric for airbags of the present invention, the resin is a silicone resin, and the resin content is 5 g / m 2 More than 50g / m 2 It is preferable that the silicone resin is applied in the range described above. Silicone resin is relatively inexpensive and can ensure excellent low air permeability. Furthermore, if the amount of resin applied is within the range described above, flexibility and storage ability can be ensured while sufficiently suppressing air permeability.
[0029] The polyester airbag fabric of the present invention is preferably made of polyester fibers having a total fineness of 200 to 555 dtex. Polyester fibers have a higher rigidity than nylon 6,6 fibers, and tend to have lower storability, but if the total fineness is 200 dtex or more, there is no need to increase the weaving density excessively, which prevents an excessive increase in the binding force between the warp and weft yarns and makes it easier to keep the storability in the airbag module within an appropriate range. Also, if the total fineness is 555 dtex or less, it is easier to prevent an excessive increase in the rigidity of the woven yarns themselves.
[0030] The polyester base fabric for airbags of the present invention is preferably composed of polyester fibers having a single yarn fineness of 6.0 dtex or less. If the single yarn fineness is 6.0 dtex or less, spinning operability can be ensured and the storability of the airbag can be ensured.
[0031] The polyester airbag fabric of the present invention preferably has a dry heat shrinkage of 3% or less, more preferably 2.5% or less, when dried for 30 minutes at 150° C. If the dry heat shrinkage falls within this range, residual shrinkage of the yarn can be sufficiently removed, and dimensional changes after the fabrication into an airbag module can be suppressed.
[0032] The polyester base fabric for airbags of the present invention preferably has a weave bending rate of 3% or less, more preferably 2.5%. With a weave bending rate in this range, the distortion of the woven fabric is small, which contributes to improving the work efficiency in the cutting and sewing processes.
[0033] The airbag fabric of the present invention preferably has a VOC content of 100 ppm or less. If the VOC content is 100 ppm or less, it can comply with environmental regulations in each country.
[0034] In the polyester fabric for airbags of the present invention, the crimp ratio of the yarns constituting the fabric is preferably 1.0% to 12.0% for both warp and weft. More preferably, it is 1.5% to 10.0% for both warp and weft, and even more preferably 2.0% to 7.0%. The present inventors have found that within this range, a polyester fabric that satisfies the ranges of the number of scrub tests after 408 hours of aging treatment at 70°C and 95% RH, the energy allowance (EA) per unit weight, and the restraining capacity utilization rate (RR) can be obtained at low cost. That is, with a crimp ratio within this range, the fabric has appropriate unevenness, which not only improves the adhesion between the polyester fabric layer and the resin layer and allows the resin to be applied uniformly, but also provides the fabric with appropriate stress-elongation characteristics and responsiveness to stress, making it easier to obtain a polyester fabric that satisfies the ranges of the energy allowance (EA) per unit weight and the restraining capacity utilization rate (RR).
[0035] When the crimp ratio is within the above range, when the base fabric is pulled in the warp and weft directions during airbag deployment, the force suddenly applied to the base fabric is stretched by the crimp, acting like a cushion and dispersing the stress. It is believed that this makes it possible to compensate for the disadvantage of polyester base fabric, which is said to be less stretchable than nylon base fabric.
[0036] The crimp ratio in the present invention was measured by the method described in JIS L1096 (2010) 8.7.2 Method B. The load used was 1 / 10 g per 1 dtex.
[0037] The polyester fibers used in the polyester base fabric for airbags of the present invention are exemplified by polyethylene terephthalate, polybutylene terephthalate, etc., and may be fibers made of copolymerized polyesters in which polyethylene terephthalate or polybutylene terephthalate is copolymerized with an aliphatic dicarboxylic acid such as isophthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, etc. as an acid component.
[0038] The polyester base fabric for airbags of the present invention has a weave density of preferably 40 threads / 2.54 cm or more in both the warp and weft directions, more preferably 46 threads / 2.54 cm or more. If the weave density is 46 threads / 2.54 cm or more, the collapse of the base fabric structure during weaving processing can be suppressed. There is no particular upper limit for the weave density, but it is preferably 70 threads / 2.54 cm or less due to restrictions on weft insertion during weaving.
[0039] In the present invention, the weave density is measured according to JIS L1096 (2010) 8.6.1. Specifically, the sample is placed on a flat table, and after removing unnatural wrinkles and tension, the number of warp and weft threads in a 2.54 cm section is counted at five different locations, and the average value for each unit length is calculated to determine the weave density.
[0040] The tensile strength of the polyester airbag fabric of the present invention is preferably 500 N / cm or more, more preferably 550 N / cm or more, from the viewpoint of mechanical properties. There is no particular upper limit to the tensile strength, but it is preferably 1000 N / cm or less, more preferably 900 N / cm or less, from the relationship with the total fineness and tensile strength of the polyester multifilaments used, and the weaving density of the airbag fabric.
[0041] In the present invention, the tensile strength of the base fabric is measured according to JIS L1096 (2010) 8.12.1. Specifically, the test piece is gripped by a tensile tester under an initial load, and the test is performed under the conditions of a test piece width of 50 mm, grip interval of 200 mm, and a pulling speed of 200 m / min, and the strength at break (N) is measured. However, those that break within 10 mm from the grip or those that break abnormally are excluded.
[0042] The aspect ratio of the cross-sectional shape of the single yarn of the polyester fiber constituting the polyester airbag fabric of the present invention is preferably 1.4 or less. The cross-sectional shape of the single yarn constituting the airbag fabric may change to a shape different from the cross-sectional shape of the single yarn of the raw yarn due to the influence of tension during processing, etc. When the cross-sectional shape of the single yarn constituting the airbag fabric has an aspect ratio of 1.4 or less, the cross section of the yarn is neatly aligned in a predetermined direction when the airbag is folded, making it easy to obtain the desired low air permeability.
[0043] The dry heat shrinkage of the polyester fiber as the raw yarn used in the manufacture of the polyester base fabric for airbags of the present invention is preferably 3% or more, more preferably 4% or more, from the viewpoint of reducing the air permeability and imparting a moderate crimp rate. On the other hand, if the dry heat shrinkage rate is too high, the thickness of the airbag base fabric after shrink processing may become thick, or the surface unevenness may be large, making it impossible to form a uniform resin layer. In addition, from the viewpoint of storage in a module, the dry heat shrinkage rate of the polyester fiber as the raw yarn is preferably 12% or less, more preferably 10% or less. By setting the dry heat shrinkage rate within the above range, a coated fabric for airbag bases having low air permeability, a moderate crimp rate, and good storage in a module can be obtained by the subsequent shrinkage treatment.
[0044] In the present invention, the dry heat shrinkage of the raw yarn is measured according to JIS L1013 (2010) 8.18.2 dry heat dimensional change rate B method. Specifically, the measurement is performed as follows. An initial load is applied to the sample, two points spaced 500 mm apart are marked, the initial load is then removed, and the sample is hung in a dryer at 180°C and left for 30 minutes. The sample is then removed and cooled to room temperature, after which the initial load is applied again. The length between the two points is measured, and the dry heat dimensional change rate (%) is calculated according to the following formula, and the average of the three measurements is taken as the dry heat shrinkage rate. ΔL=L-500 / 500×100 ΔL: Dry heat shrinkage rate (%) L: Length between two points (mm)
[0045] Hereinafter, manufacturing methods suitable for obtaining the polyester base fabric for airbags of the present invention will be described in detail, but the polyester base fabric for airbags of the present invention is not limited to fabrics manufactured by these manufacturing methods.
[0046] The warp tension when weaving the polyester base fabric for airbags of the present invention is preferably 120 to 200 cN / thread. If the warp tension is 120 cN / thread or more, the warp threads are less likely to slacken during weaving, which leads to defects in the fabric and loom stoppages, and the crimp rate can be controlled within an appropriate range. On the other hand, if the warp tension is 200 cN / thread or less, it is easy to avoid excessive load being applied to the warp threads, which leads to defects in the fabric.
[0047] Since it is difficult to increase the crimp rate of polyester fiber compared to nylon 6,6 fiber, in weaving the polyester base fabric for airbags of the present invention, it is preferable to set the dwell angle of the reed to 60 to 120° in order to increase the crimp rate while suppressing defects in the base fabric. If the dwell angle of the reed is outside this angle range, there is a concern that the flying area of the weft yarn cannot be secured, and defects in the base fabric may occur frequently.
[0048] Furthermore, in order to improve the crimp rate in the warp direction and to suppress defects in the base fabric, it is preferable to install a guide roll between the back roller and the heddles so as to lift the warp yarns 20 to 50 mm from the warp line. If the warp line is out of this position range, there is a concern that defects in the base fabric will occur frequently due to the difference in tension between the upper thread and the lower thread.
[0049] In addition, it is preferable to attach a positive easing mechanism to the back roller in order to improve the crimp rate in the warp direction while maintaining the strength of the base fabric. The easing amount in the positive easing mechanism is preferably 5 to 7.5 mm, and the easing timing is preferably set to the cross timing of the loom ±30°. When the positive easing mechanism is used within this setting range, it is possible to prevent excessive tension from being applied to the warp yarns during the shedding movement, preventing excessive load from being applied to the yarns and maintaining the strength of the base fabric. In addition, since the warp yarns can be shed with an appropriate tension, the crimp rate in the warp direction can be improved. In addition, it is preferable to adjust the pump diameter, stroke, and nozzle diameter in a direction to increase the yarn conveying force in order to improve the crimp rate in the warp direction.
[0050] Since it is more difficult to increase the crimp rate of polyester fibers compared to nylon 6,6 fibers, it is preferable to set the winding tension in the winder in the weaving process to 250 to 1500 N. Since polyester base fabrics are more rigid than nylon 6,6 base fabrics and the winding tension can be set lower than that of nylon 6,6, the crimp rate can be improved by setting the winding tension low enough to prevent wrinkles or slack during winding.
[0051] Examples of shrinkage include hot water processing and heat setting processing represented by pin tenter, but hot water processing using hot water for shrinkage is particularly preferred. When using hot water, a method of immersing the fabric obtained by the above weaving in hot water or a method of spraying hot water on the fabric can be adopted. The temperature of the hot water is preferably about 80 to 100 ° C, more preferably 95 ° C or higher. When the temperature of the hot water is this temperature, the green machine after weaving shrinks efficiently and the crimp rate of the base fabric can be improved, which is preferable. The fabric obtained by weaving may be dried once and then shrunk, but in terms of production costs, it is advantageous to perform shrinkage processing on the fabric obtained by weaving without drying, and then perform dry finishing.
[0052] The drying temperature of the hot air drying process in the manufacturing process of the polyester base fabric for airbags of the present invention is preferably such that the surface temperature of the base fabric at the outlet of the dryer is 100°C to 150°C. If the surface temperature of the base fabric is within this range, the base fabric can be sufficiently dried, and the crimp rate of the base fabric can also be improved by the hot air. In addition, it is preferable to adjust the temperature of the hot air dryer so that the surface temperature of the base fabric at the outlet of the dryer is in the range of 100°C to 150°C, and therefore it is preferable to set the temperature of the hot air dryer to 130°C to 180°C.
[0053] The coating resin used in the coating step in the manufacturing process of the polyester base fabric for airbags of the present invention is preferably an elastomer resin having heat resistance, cold resistance, and flame retardancy, but silicone-based resins are the most effective. Specific examples of silicone-based resins include addition polymerization type silicone rubbers. For example, dimethyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl silicone rubber, trimethyl silicone rubber, fluoro silicone rubber, methyl silicone resin, methyl phenyl silicone resin, methyl vinyl silicone resin, epoxy modified silicone resin, acrylic modified silicone resin, polyester modified silicone resin, etc. are included. Among them, methyl vinyl silicone rubber is preferred because it has rubber elasticity after curing, has excellent strength and elongation, and is also advantageous in terms of cost.
[0054] In the polyester airbag fabric of the present invention, the viscosity of the silicone resin used is very important. The viscosity of the silicone resin is preferably 10 Pa·sec or more, more preferably 15 Pa·sec or more. There is no particular upper limit, but if the resin viscosity is greater than 40 Pa·sec, the resin cannot be present in the mesh between the warp and weft yarns on the uncoated surface, which is essential for improving the tensile strength of the polyester fabric after coating. As long as the viscosity can be adjusted within the above range, either a solvent-based or solventless system may be used, but a solventless system is preferable in consideration of the impact on the environment. In the present invention, in the case of a resin composition containing additives other than resin, the viscosity of the resin composition is also defined as the "resin viscosity".
[0055] In addition, it is preferable that the film strength of the resin is 3 MPa or more and the film elongation is 250% or more. Generally, the film strength and the film elongation are linked physical properties, but when the film elongation is 250% or more, if the resin is present in the mesh part of the warp and weft, the resin will elongate, and the conformability of the coated fabric during the scrub test will improve, thereby achieving high kneading resistance. A more preferable range of the film elongation is 300% or more. The upper limit of the film strength is not particularly limited, but it is preferably 10 MPa or less. In addition, a sample for measuring the film strength and elongation of the silicone resin is actually coated on an airbag fabric and prepared according to the conditions (temperature, time, pressure) when forming the film. Specifically, a resin film of a constant thickness of 0.5 mm is prepared from the silicone resin, and cured at 190°C for 2 minutes by hot air irradiation, and a tensile test is performed.
[0056] The hardness of the resin is preferably 40 or less as measured using a Shore A hardness tester according to ASTM D2240. More preferably, it is 38 or less. When the hardness is 40 or less, the resin is deformed during the scrub test, and the base fabric has high knead resistance because of the improved followability, similar to the resin elongation. The lower limit is not particularly limited, but is usually 25 or more.
[0057] In the polyester base fabric for airbags of the present invention, the average resin thickness in the weft direction at the top of the coated fabric surface is preferably 4 μm or more, more preferably 6 μm or more. The top refers to the part of the warp or weft where the resin film thickness is the thinnest. In the present invention, it is preferable that the resin is not allowed to penetrate too far into the fabric, and that the resin is present in a relatively uniform film thickness throughout the entire fabric on the coated surface, especially at the top of the fabric. If the thickness is less than 4 μm, there is a possibility that the ventilation inhibition and flame retardancy will not be satisfied. There is no particular upper limit, but if it is 25 μm or more, it becomes difficult to apply the resin by knife coating.
[0058] In the polyester base fabric for airbags of the present invention, the average resin thickness in the weft direction at the top of the coated fabric surface is preferably 4 μm or more, more preferably 6 μm or more. The top refers to the part of the warp or weft where the resin film thickness is the thinnest. In the present invention, it is preferable that the resin is not allowed to penetrate too far into the fabric, and that the resin is present in a relatively uniform film thickness throughout the entire fabric on the coated surface, especially at the top of the fabric. If the thickness is less than 4 μm, there is a possibility that the ventilation inhibition and flame retardancy will not be satisfied. There is no particular upper limit, but if it is 25 μm or more, it becomes difficult to apply the resin by knife coating.
[0059] In the present invention, the resin can be applied by a conventional method, but knife coating, particularly knife-on-air coating, is most preferred in terms of ease of adjusting the amount of coating and the effect of contamination by foreign matter (projections). In the knife-on-bed method, the resin can easily penetrate into the fabric, but it is difficult to have the resin present at the top of the fabric on the coated surface, making it impossible to achieve the breathability suppression originally required of coated fabrics. In the present invention, the knife used in knife coating can have a semicircular, angular, or other blade tip shape.
[0060] In knife coating by the knife-on-air method, the tension of the base fabric in the direction of travel is preferably 500 to 2000 N / m, and particularly preferably 1000 to 1800 N / m. If the tension of the base fabric in the direction of travel is less than 500 N / m, the selvage of the base fabric becomes bulky, and the coating amount at the center and end of the base fabric is likely to differ greatly. On the other hand, if the tension of the base fabric in the direction of travel exceeds 2000 N / m, the gap between the warp and weft yarns is filled, and the resin cannot be present in the mesh between the warp and weft yarns on the non-coated surface. In addition, the base fabric is stretched during coating, and the crimp rate of the base fabric may decrease.
[0061] In the present invention, it is important that the knife pushing amount is 1 to 6 mm. The knife pushing amount corresponds to the amount by which the knife is pushed downward from the height of the upper surface of the bed located immediately before the bed in the knife-on-air method, which is set to 0 mm. It is more preferably 1.5 to 4.5 mm. If the knife pushing amount is less than 1 mm, the resin cannot be present in the mesh portion between the warp and weft yarns on the non-coated surface, which is the object of the present invention. If it is 6 mm or more, the resin can easily penetrate into the inside of the fabric, but it becomes difficult to have the resin present on the top of the fabric on the coated surface, and the ventilation inhibition originally required for the coated fabric cannot be achieved.
[0062] As a method for drying and curing the coating agent after application, a general heating method such as hot air, infrared light, microwave, etc. can be used. Regarding the coating curing temperature and curing time, it is preferable that the surface temperature of the base fabric at the outlet of the heat treatment machine is 165°C to 200°C. If the surface temperature of the base fabric is within this range, not only can the silicone resin be cured sufficiently, but also the crimp rate of the base fabric can be improved by heat. In addition, it is preferable that the temperature of the heat treatment machine is set to a range of 165°C to 200°C so that the surface temperature of the base fabric at the outlet of the heat treatment machine is 200°C to 220°C.
[0063] The airbag using the polyester airbag fabric of the present invention is preferably used for, for example, a driver's seat airbag, a passenger seat airbag, a curtain airbag, a side airbag, a knee airbag, a seat airbag, a reinforcing fabric, etc. Therefore, these products are also included in the scope of the present invention. As an airbag using the airbag fabric of the present invention, an airbag that requires a part that is particularly long in the weft direction is preferable because the coated airbag fabric of the present invention is less likely to cause misalignment after sewing when cutting a part that is long in the weft direction. Specifically, a side curtain airbag is preferable. In addition, since the coated airbag fabric of the present invention is particularly excellent in storage capacity, an airbag that requires particularly high storage capacity is also preferable. Specifically, a driver's seat airbag, a passenger seat airbag, and a curtain airbag are preferable. As an airbag using the airbag fabric of the present invention, an airbag that requires a part that is long in the weft direction and storage capacity is more preferable. Specifically, a side curtain airbag is more preferable. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be modified within the scope of the above and below, and all of these are included in the technical scope of the present invention. The test methods for various properties used in the following examples are as follows.
[0065] <Weight of base fabric> Measurements were made in accordance with JIS L1096 (2010) 8.3.2. Two test pieces measuring approximately 200 mm x 200 mm were taken from the sample, and the bone dry mass (g) of each was measured to determine the mass per m2 (g / m2), and the average value was calculated to obtain the basis weight.
[0066] <Weave density of base fabric> Measurements were performed based on JIS L1096 (2010) 8.6.1. The sample was placed on a flat table, and after removing any unnatural wrinkles or tension, the number of warp and weft threads in a 2.54 cm section was counted at five different locations, and the average value for each unit length was calculated to determine the density.
[0067] <Thickness of base fabric> Measurements were taken based on JIS L1096 (2010) 8.4. Specifically, five different points on the sample were measured using a thickness gauge under a pressure of 23.5 kPa, after waiting 10 seconds to allow the thickness to settle, and the average value was calculated.
[0068] <Tensile strength and elongation at break of base fabric> Measurements were made based on JIS K 6404-3:1999 6. Test method B (strip method). The test piece was gripped by a tensile testing machine under initial load, and the test was performed under the conditions of a test piece width of 50 mm, grip interval of 200 mm, and tensile speed of 200 m / min, and the strength (N) and elongation (mm) at the time of breaking were measured. However, specimens that broke within 10 mm from the grip or abnormally broken specimens were excluded.
[0069] <Energy allowance per unit weight> The allowable energy per unit weight was measured based on JIS K 6404-3:1999 6. Test method B (strip method), by removing the yarn from both sides of the width in each warp and weft direction to obtain three test pieces of width 30 mm and length 300 mm. Using a constant-speed tension tester, the test pieces were stretched to a stress of 120 N / cm with a gripping distance of 150 mm and a tensile speed of 200 mm / min, and immediately thereafter, the test pieces were relaxed at a tensile speed of 200 mm / min until the stress reached 0 N / cm. Based on the obtained stress and elongation data and the following formula (3), the area enclosed by the curve from the start to the end of the stretch was calculated. This area corresponds to the amount of energy that the base fabric can tolerate during the process from the start to the end of the stretch. Based on the results of integrating the calculated areas, the average values in the warp and weft directions were calculated, and the average values were divided by the surface area of the fabric between the chucks (30mm x 150mm) to calculate the hysteresis energy per unit surface area. The energy allowance in the warp direction (EW) and the energy allowance in the weft direction (EF) were calculated by dividing the hysteresis energy per surface area of the fabric between the chucks in the warp and weft directions by the fabric weight. Energy absorption at any point in time = {(n+1th elongation) - (nth elongation)} × (n+1th stress) (3) Here, the nth elongation is the value of the elongation in the warp or weft direction at any time in a series of processes from applying stress in the warp or weft direction to relaxing it, and the n+1th elongation (stress) is the value of the elongation (stress) in the warp or weft direction 50 msec after the value of the nth elongation (stress). According to formula (3), the energy allowance at any time in a series of processes from applying stress in the warp or weft direction to relaxing it is calculated. Therefore, the energy allowance at each time point obtained from the start to the end is added up, and the total value is divided by the surface area between the chucks (30 mm x 150 mm) to calculate the hysteresis energy per unit surface area. Furthermore, the energy allowance in the warp direction (EW) and the energy allowance in the weft direction (EF) can be calculated by dividing the hysteresis energy per surface area between the chucks of the base fabric in the warp and weft directions by the basis weight.
[0070] <Restraint ability usage rate> The restraint capacity utilization rate was determined based on JIS K 6404-3:1999 6. Test method B (strip method), and for each of the warp and weft directions, yarns were removed from both sides of the width to obtain three test pieces of 30 mm width and 300 mm length. These were then stretched in a constant-speed tension-type testing machine with a gripping distance of 150 mm and a tensile speed of 200 mm / min until the stress reached 120 N / cm. Based on the obtained elongation data, the above-specified elongation at break of the base fabric, and the following formula (4), the restraint capacity utilization rate in the warp direction (RW) and the restraint capacity utilization rate in the weft direction (RF) were calculated. Elongation at 120 N / cm / Elongation at break (4)
[0071] <Number of initial scrub tests for base fabric> Calculation was based on ISO5981. Specifically, five test pieces were taken from the sample, each test piece was fixed to a scrub tester, and the test was performed under an initial load of 1 kgf. After the test, the degree of peeling of the coating of the sample was visually confirmed. The number of times just before the coating of the sample peeled off and the base fabric surface was exposed, that is, the limit number of times the coating of the sample did not peel off, was calculated in increments of 50, and the average value was calculated as the number of scrub tests.
[0072] <Number of scrub tests on base fabric after aging for 408 hours at 70℃ 95% RH> The sample was subjected to aging treatment at 70°C and 95% RH for 408 hours using a low-temperature thermohygrostat PL-2J manufactured by ESPEC Co., Ltd., and the aging treatment was used to calculate the scrub test results based on ISO5981. Specifically, five test pieces were taken from the sample, and each test piece was fixed to a scrub tester and tested under an initial load of 1 kgf. The peeling of the coating of the sample after the test was visually confirmed. The number of times just before the coating of the sample peeled off and the base fabric surface was exposed, that is, the limit number of times the coating of the sample did not peel off, was calculated in increments of 50, and the average value was calculated to be the number of scrub tests.
[0073] <Dry heat shrinkage rate of base fabric> The measurement was performed in accordance with JIS L1096 (2010) 8.38.3. Specifically, two test pieces of approximately 250 mm x 250 mm were taken from the sample, and marks were made at three equally spaced locations in the vertical and horizontal directions over a 20 cm length starting from 2.5 cm from the cut end, and the length between the marks was recorded as the length before treatment. The sample with the recorded length was dried in a thermostatic oven at 150°C for 30 minutes, and the treated sample was taken out, and the length between the marks was recorded as the length after treatment in the same way as before treatment, and the dry heat shrinkage was calculated based on the following formula (5). Dry heat shrinkage rate (%)=(b―a) / a × 100 ···(5) a: Length before treatment (cm), b: Length after treatment (cm)
[0074] <Curve twist rate of base fabric> Measurements were made based on JIS L1096 (2010) 8.12.A. Specifically, one test piece measuring 10 cm in length across the entire width was taken from the sample, and a weft line AB was drawn from one edge A along the weft thread to the other edge B as shown in Figure 1. Next, a line was drawn from A perpendicular to the edge, and the point where it intersects with the other edge was designated C, and the length a (cm) of line AC (width) was calculated, and the maximum skew distance (cm) between AC shown in Figure 1 was measured, and the fabric bend ratio was calculated based on the following formula (6). Fabric curl (%) = b / a × 100 (6) a: width (cm), b: maximum skew distance (cm)
[0075] <VOC content of base fabric> Measurements were made in accordance with VDA278. Specifically, 30 mg ± 5 mg of sample was precisely weighed, and the sample was heated to 90°C for 30 minutes. The components generated were measured by thermal desorption-GCMS and quantified in toluene equivalent. The same measurement was performed twice, and the higher value was regarded as the VOC content.
[0076] <Crimp rate of base fabric> The measurement was performed according to the method described in JIS L1096 (2010) 8.7.2 Method B. The load used was 1 / 10 g per 1 dtex.
[0077] <Amount of coating agent applied to base fabric> After the resin was cured, the coated fabric was accurately sampled to a size of 5 cm square and immersed in a solvent that dissolves only the fibers that make up the base fabric (hexafluoroisopropanol in the case of polyester fibers) to dissolve the base fabric. Next, only the silicone coating layer, which is insoluble, was collected and washed with acetone. After drying in a vacuum, the sample was weighed. The coating amount was 1 m 2 Mass per unit (g / m 2 ) is expressed as
[0078] <Total fineness of raw yarn> Measurements were made in accordance with JIS L1013 (2010) 8.3.1. Specifically, a sample with an exact length of 90 cm was taken with an initial load applied, its bone dry mass was measured, and the corrected fineness (dtex) was calculated based on the following formula (7), and the average value of five measurements was taken as the total fineness. F0=1000×m / 0.9×+(100+R0) / 100 ···(7) F0: normal fineness (dtex), L: length of sample (m), m: bone dry mass of sample (g), R0: official moisture content (%)
[0079] (Example 1) Polyester multifilament raw yarn with a fineness of 555 dtex / 96f (single yarn cross section is round) was used for the warp and weft, and the set weave density for both warp and weft was 51 threads / 2.54 cm. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 98°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the outlet of the dryer (measured with a non-contact thermometer) was 120°C. Next, a solventless silicone resin composition with a resin viscosity of 18 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 26 g / m 2 The coating conditions were adjusted to meet the conditions in Table 1 so that the coating temperature would be 170°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0080] (Example 2) Polyester multifilament raw yarn with a fineness of 470 dtex / 144f (single yarn cross section is round) was used for the warp and weft, and the set weave density for both warp and weft was 51 threads / 2.54 cm. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 98°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the outlet of the dryer (measured with a non-contact thermometer) was 120°C. Next, a solventless silicone resin composition with a resin viscosity of 18 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 24 g / m 2The coating conditions were adjusted to meet the conditions in Table 1 so that the coating temperature would be 170°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0081] (Example 3) Polyester multifilament yarn with a fineness of 470 dtex / 96f (single yarn cross section is round) was used for the warp and weft, and the weave density was set to 46 threads / 2.54 cm for both the warp and weft. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 98°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the dryer outlet (measured with a non-contact thermometer) was 120°C. Next, a solventless silicone resin composition with a resin viscosity of 18 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 15 g / m 2 The coating conditions were adjusted to meet the conditions in Table 1 so that the coating temperature would be 170°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0082] (Example 4) Polyester multifilament yarn with a fineness of 470 dtex / 96f (single yarn cross section is round) was used for the warp and weft, and the weave density was set to 46 threads / 2.54 cm for both the warp and weft. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 98°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the dryer outlet (measured with a non-contact thermometer) was 120°C. Next, a solventless silicone resin composition with a resin viscosity of 50 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 15 g / m 2The coating conditions were adjusted to meet the conditions in Table 1 so that the coating temperature would be 170°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0083] (Example 5) Polyester multifilament raw yarn with a fineness of 470 dtex / 144f (single yarn cross section is round) was used for the warp and weft, and the set weave density for both warp and weft was 58.5 threads / 2.54 cm. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 98°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the outlet of the dryer (measured with a non-contact thermometer) was 120°C. Next, a solventless silicone resin composition with a resin viscosity of 18 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 25 g / m 2 The coating conditions were adjusted to meet the conditions in Table 1 so that the coating temperature would be 170°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0084] (Example 6) Polyester multifilament raw yarn with a fineness of 555 dtex / 144f (single yarn cross section is round) was used for the warp and weft, and the set weave density for both warp and weft was 54.5 threads / 2.54 cm. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 98°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the outlet of the dryer (measured with a non-contact thermometer) was 120°C. Next, a solventless silicone resin composition with a resin viscosity of 18 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 25 g / m 2The coating conditions were adjusted to meet the conditions in Table 1 so that the coating temperature would be 170°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0085] (Comparative Example 1) Polyester multifilament raw yarn with a fineness of 560 dtex / 96f (single yarn cross section is round) was used for the warp and weft, and the weave density was set to 46 threads / 2.54 cm for both warp and weft. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 65°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the dryer outlet (measured with a non-contact thermometer) was 90°C. Next, a solventless silicone resin composition with a resin viscosity of 50 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 29 g / m 2 The coating conditions were adjusted to the conditions shown in Table 1 so that the coating temperature would be 160°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0086] (Comparative Example 2) Polyester multifilament raw yarn with a fineness of 560 dtex / 96f (single yarn cross section is round) was used for the warp and weft, and the weave density was set to 46 threads / 2.54 cm for both warp and weft. The weaving conditions were as shown in Table 1. The fabric was woven in a plain weave using a water jet loom, and then passed through a hot water shrinkage bath at 65°C without drying. Subsequently, the fabric was passed through a drying process so that the surface temperature of the base fabric at the dryer outlet (measured with a non-contact thermometer) was 90°C. Next, a solventless silicone resin composition with a resin viscosity of 50 Pa sec was applied to one side of the fabric using a knife-on-air method at a coating amount of 18 g / m 2The coating conditions were adjusted to the conditions shown in Table 1 so that the coating temperature would be 160°C at the exit of the heat treatment machine (measured with a non-contact thermometer), and a coated fabric was obtained. Details of the manufacturing conditions are shown in Table 1, and the physical properties of the obtained coated fabric are shown in Table 2.
[0087] [Table 1]
[0088] [Table 2] [Industrial Applicability]
[0089] The present invention relates to a polyester base fabric for airbags that has high restraint performance for receiving an occupant when deployed while maintaining the mechanical properties of an airbag, and furthermore, maintains the performance at a high level even when it changes over time. Therefore, it is possible to popularize relatively low-cost polyester airbags, which will greatly contribute to the development of the industry. [Explanation of symbols]
[0090] A: Point on one edge B: Other ear tip point C: Draw a line perpendicular to the edge from A and cross it with the other edge. a: Length of line AC (width) b: Maximum skew distance between AC
Claims
[Claim 1] A polyester base fabric for airbags having a resin on at least one surface thereof, The crimp rate of the yarns constituting the polyester base fabric for airbags is set to be 100% for both the warp and weft yarns. A polyester base fabric for airbags, characterized in that the content of the polymer in the base fabric is 1.0% to 12.0%.
Citation Information
Patent Citations
A kind of coated fabric for airbag
CN103132333B